Histological Evaluation of the Effect of Local Application of Grape Seed Oil on Healing Process of Extracted Tooth Socket in Rabbits - Abd Alrazaq Hassan, Manar; MH AL-Ghaban, Nada (Diyala Journal of Medicine, 2019)
Background: The process of wound healing in the socket include the healing of wounds in soft tissues, and healing of the bone. The herbal medicament widely used in the healing of different wounds. The benefit of Grape seed oil due to their anti-oxidant and anti-inflammatory effect. Objective: Histological evaluation the effects of local application of grape seeds oil in the healing process of dental socket after tooth extraction and compared the result with normal healing process. Patients and Methods: Thirty six New Zeland male rabbits were used in this study, the upper right central incisor was extracted for each rabbit ,then the rabbits were divided into 3 main groups ;Control group: 12 rabbits , the socket heal spontaneously , sponge group:12 rabbits ,the socket treated with absorbable hemostatic sponge and grape seed oil group: 12 rabbits, the socket treated with local application of 0.5 ml/Kg of B.W. grape seeds oil fixed by absorbable hemostatic sponge. Then each group were divided into two sub group according to the healing intervals 2 and 4 week (6 rabbits from each group). Histological evaluation performed by section stained with hematoxylin and eosin (H&E), and histomorphometric analysis for assessment of osteoclasts ,osteoblasts, osteocytes , trabecular no., trabecular area and marrow space area by Image J. software. Results: The histological and histomorphometric results of present study showed enhancement of healing process in grape seeds oil and sponge group after tooth extraction by activation of large number of osteoblasts, osteocytes and osteoclasts that started from apical part, then middle part finally in coronal part of the socket. Conclusion: Grape seed oil accelerate the healing process after locally treated tooth socket and assessed in new bone formation. DOI:https://doi.org/10.26505/DJM.17024670515